(untitled) (Palíndromo, 2020)
This expanded summary is the result of a research with Digital Woodcut that took place in the city of Marabá-PA, where due to the peculiarities of the site, a permutation was done between historical woodcut and its fundaments and the Digital process. Therefore, two references of artists who produce their works with Digital Woodcut will be approached, then what distinguishes this research in terms of the references will be delimited, and finally the practical work that originated it as method and content.